How Different are Assessments of Independence and Devolution Max? An Analysis of the Role of National Identity and Party Affiliation. Issue 1 (February 2014) - van der Zwet, Arno; McAngus, Craig
<x xml:space="preserve">Abstract</x> Although the actual constitutional preferences of the Scottish public have been analysed at great length, the assessments of how different constitutional scenarios will perform in future have received little attention. This paper aims to address this by examining how well the public think an independent and a devolution max (DevoMax) Scotland will perform, looking specifically at the role of national identity and party affiliation. Factor analysis is used to construct a latent 'performance assessment' variable, and this latent variable is used extensively in the analysis. The paper finds that, on the whole, there is little difference between performance assessments of independence and DevoMax. However when considering national identity it can be seen that although Scottish identifiers by and large assess independence and DevoMax equally, strong British identifiers do not; they are considerably less negative about DevoMax. Furthermore, although the patterns of performance assessment are unsurprising in terms of party affiliation, Labour affiliates are, on the whole, more positive about the future performance of an independent Scotland than might have been expected. Furthermore, linear regression shows that the 'identity' variables have a more powerful effect on perceptions of independence than DevoMax. These findings suggest that an element of 'heuristic shortcutting' might be taking place.